Risk factors of non-typhoidal Salmonella gastroenteritis in hospitalised young children: a case-control study - Pei Yee Woh; May Pui Shan Yeung; E Anthony S Nelson; William Bernard III Goggins (BMJ Publishing Group, 2021)
Objective To explore risk factors associated with non-typhoidal Salmonella gastroenteritis in young children in Hong Kong.Design A case-control study.Setting Paediatrics wards at three public hospitals in Hong Kong.Participants Cases were children aged above 30 days to below 5 years hospitalised for gastroenteritis at three public hospitals in Hong Kong with culture confirmed non-typhoidal Salmonella infection. Controls were age-matched (±2 months) children admitted for a reason other than gastroenteritis.Main outcomes measures A face-to-face interview by using standardised questionnaire on exposures 3 days prior to illness. Adjusted OR (aORs) and 95% CIs were calculated using multivariable logistic regression.Results A total of 102 cases and 204 age-matched controls were included in the analysis. Multivariable logistic regression revealed that having food purchased from places other than a supermarket, that is, from wet market/restaurant/farm (aOR, 2.64; 95% CI, 1.03 to 6.77; p=0.044) was a significant risk factor for non-typhoidal Salmonella infection. Having a household member with gastroenteritis symptoms (aOR, 2.03; 95% CI, 0.94 to 4.39; p=0.072) was of borderline significance and playing at a children's indoor playroom was a protective factor (aOR, 0.28; 95% CI, 0.09 to 0.85; p=0.024).Conclusions Consumption of food purchased from places other than a supermarket was the identified determinant factor for non-typhoidal Salmonella gastroenteritis in Hong Kong. Parents/caregivers should be alerted to this risk when choosing foods for their young children. The protective effect of playing in an indoor playroom could be confounded by socioeconomic factors and further investigation is required to better understand its potential implication. There was some support for person-to-person transmission and good family hygiene needs to be emphasised.